2017
DOI: 10.1038/s41598-017-13109-5
|View full text |Cite
|
Sign up to set email alerts
|

Preference for novel faces in male infant monkeys predicts cerebrospinal fluid oxytocin concentrations later in life

Abstract: The ability to recognize individuals is a critical skill acquired early in life for group living species. In primates, individual recognition occurs predominantly through face discrimination. Despite the essential adaptive value of this ability, robust individual differences in conspecific face recognition exist, yet its associated biology remains unknown. Although pharmacological administration of oxytocin has implicated this neuropeptide in face perception and social memory, no prior research has tested the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…The relationship between the number of reciprocal friendships and plasma OT was best described by a U-shaped quadratic function (middle- and high-ranking juveniles with either low or high numbers of reciprocal friendships had higher OT levels) (Weinstein et al, 2014). Recently Madrid et al (2017) showed that the preference for novel faces of infant rhesus monkeys predicted the concentration of OT in the CSF. The ability to recognize others is an essential social behavior in primates (Gothard & Hoffman, 2009; Leonard, Blumenthal, Gothard, & Hoffman, 2012), and deficits in facial processing are early predictors of social deficits later in life (Sclafani et al, 2016).…”
Section: Studies Of Oxytocin In Non-human Primatesmentioning
confidence: 99%
“…The relationship between the number of reciprocal friendships and plasma OT was best described by a U-shaped quadratic function (middle- and high-ranking juveniles with either low or high numbers of reciprocal friendships had higher OT levels) (Weinstein et al, 2014). Recently Madrid et al (2017) showed that the preference for novel faces of infant rhesus monkeys predicted the concentration of OT in the CSF. The ability to recognize others is an essential social behavior in primates (Gothard & Hoffman, 2009; Leonard, Blumenthal, Gothard, & Hoffman, 2012), and deficits in facial processing are early predictors of social deficits later in life (Sclafani et al, 2016).…”
Section: Studies Of Oxytocin In Non-human Primatesmentioning
confidence: 99%
“…However, other studies in humans using attentional capture techniques do strongly suggest the modulation of early perceptual processing by OT [Ellenbogen et al, 2012], and similar studies in monkeys have also indicated the effects of OT in perceptual processing, although these studies generally find that OT diminishes the salience of distracting social stimuli in these distractor-based paradigms [Ebitz et al, 2013; Landman et al, 2014]. A recent study further indicated that facial recognition ability in male infant macaques correlates with OT levels in cerebrospinal fluid later in life [Madrid et al, 2017].…”
Section: Ot In the Context Of Multistage Social Decision-makingmentioning
confidence: 99%
“…A 100‐Hz tone was presented 250 milliseconds prior to test trials in order to orient the animal's gaze. All video stimuli were photographs of novel rhesus macaque monkeys and can be found as Supplementary Material to Madrid et al (). The principal outcome measure was the proportion of looking time spent viewing the novel pictures, which was calculated by taking the duration that the animals looked at the novel stimuli for the two test trials for each problem, and dividing by the duration of time animals looked at either the novel or familiar stimuli.…”
Section: Methodsmentioning
confidence: 99%